Systematic Risk and Non-Systematic Risk Impact on Stock Returns in Health Sector Companies - Reistiawati Utami; Mahesa Vicky Satria Ramadhan Lihu (Journal of Business Transformation and Strategy, 2024)
Abstract: When an investor decides to invest in the capital market, investor would be understood that the investment will bring profits and contain risks. In the Capital Market, risk can be classified into Systematic Risk (Market Risk), which is the risk that is experienced by all issuers and cannot be diversified, and Non-Systematic Risk, which is the risk that exists in one particular company or industry so that it can still be minimized or diversified. This research aims to prove the effect of systematic and non-systematic risk on stock returns during the Covid 19 pandemic and after, where the moments that cause systematic risk and also non-systematic risk occur together. The Health Sector is a sector that experiences a direct impact because it acts as a basis for defense against the Covid 19 Epidemic. Systematic Risk uses the Stock Beta, Interest Rate, Foreign Exchange, and Inflation, while non-systematic Risk uses the Solvency Ratio (DER) and Profitability Ratio (ROE). Using a purposive sampling technique, 15 health sector companies were selected during 2018 - 2023. Statistical analysis carried out using Smart PLS 4.0 resulted that Systematic Risk and Non-Systematic Risk did not affect Share Returns of Health Sector Companies in the 2018 - 2023 period Keywords: Systematic Risk, Non-Systematic Risk, Stock Returns